Impact of green human resource management practices on employee engagement from the perspective of banking employees. (23rd February 2023) - Wang, Linqing; Wang, Ruiling; Wu, Jing
The scope of green human resource management (GHRM) has gotten intense concern from researchers over the last decade. However, little work has been accomplished in taking GHRM practices to attain distinct goals of the workplace, such as employee engagement (EE). Using random sampling and dispersion of the questionnaire among HR managers (n = 432) and by utilising SEM modelling, this study endorsed that employee engagement is anticipated to be improved by employing GHRM into practices within three ways, green appraisal practices (GAP), green employee involvement practices (GEIP) and green training practices (GTP). The profound investigation demonstrated the positive nexus of each GHRM practice (i.e., GAP, GEIP and GTP) on employee engagement drawing on resource-based theory. The present findings assure a significant contribution to the literature on GHRM and employee engagement along with several implications both practical and managerial. This study promotes GHRMs' notion and uplifts firms seeking employee engagement toward a particular workplace. Some future potential are reported for worldly scholars based on current deficiencies of the study.